COVID 19 MEMES AS A TEACHING TOOL: ITS IMPLEMENTATION FOR TEACHING DESCRIPTIVE TEXT - Shania Salma; Faiza Hawa; Siti Musarokah (ETERNAL (English Teaching Journal), 2021)
This study is an attempt to reveal the implementation of Covid 19 memes in teaching descriptive text for secondary high school students in Tahunan Jepara. In addition, this study also aims to find out the problems the students face during the process of implementing the memes for teaching writing. Since Covid 19 pandemic hinder everyone to gather in a period of time, so it is possible for the researchers to process this research online. It means that the distribution of instrument for collecting the data is done online. The data for this descriptive qualitative study were taken from both the students and the English teacher. 32 students were involved in this study. Questionnaire was distributed to students to gain some information related to the problems they experienced during the process of learning, while indirect interview was given only to the teacher to know how he or she implemented the Covid 19 memes for teaching descriptive text. The data were then processed by elaborating them descriptively. Then, the researchers did data reduction, data display and as final step the researchers draw conclusion of all. The results showed that Covid 19 memes inspired the students for ideas for writing descriptive text. It was exactly 88% students said so. While the rest of 12% said otherwise.  Related to the problems in learning using Covid 19 memes, 78% students did not have any problems with it. While the rest of it said that they had problems in naming the terms (13%), in understanding the meme’s content (6%), and in elaborating ideas in English sentences (3%)